Empowering Elementary School Children: Increasing Self-Efficacy Through Traditional Game-Based Counseling - Edy, Edy Irawan; Syarifuddin Dahlan; Farida Ariyani; Een Yayah Hanillah (ILIN Education Indonesia, 2024)
This research investigates the efficacy of a counseling model that utilizes traditional games to increase self-efficacy in elementary school children. Using a developmental approach rooted in the Borg and Gall model, this research develops a counseling framework that centers on traditional games as an interactive medium for client involvement. Specifically, this research pioneers the exploration of traditional play-based counseling interventions specifically designed to improve children's self-efficacy; an area hitherto unexplored in the literature. Traditional play, chosen for its inherent capacity to facilitate emotional expression and character development in children, serves as an appropriate channel for therapeutic interaction. Through rigorous testing and data analysis, the efficacy of the developed counseling model was confirmed, proven by its high validity and practical usefulness. The results show the effectiveness of the model in increasing the level of self-efficacy in all dimensions so that this model is declared worthy as an intervention strategy because it is easy to access, culturally appropriate, and age-appropriate for elementary school children.